Experimental and numerical investigations on concrete-filled double-tubular slender columns under axial and eccentric loading. (February 2023) - Wang, Wen-Da; Ji, Sun-Hang; Shi, Yan-Li
Abstract: This paper presents an experimental and numerical investigation on concrete-filled double-tubular (CFDT) slender columns under axial and eccentric loading. 16 circular and square specimens are tested, comprising 14 CFDT columns and 2 concrete-filled steel tubular (CFST) columns. Various parameters, including the inner steel tube ratio, the load eccentricity and slenderness ratio, are considered to investigate their effects on the failure models, the ultimate capacity and ductility of CFDT slender columns. Test results show that slender CFDT columns exhibit higher bearing capacity and superior ductility than CFST columns owing to the presence of inner steel tubes. The ultimate capacity of CFDT columns enhances as the inner steel tube ratio increases, but declines as the slenderness ratio rises. The finite element analysis (FEA) model of CFDT slender columns is also developed and calibrated against the test results, and is then employed to examine the full-range behaviour of CFDT columns under axial and eccentric loading and carry out a parametric study. Graphical abstract: Unlabelled Image Highlights: Very limited studies on CFDT slender columns under eccentric loading are available. Sixteen CFDT and CFST slender columns under axial and eccentric loading are tested. The FEA model is developed to analyze the full-range behaviour of CFDT slender columns.